Lipid-coated mesoporous silica microparticles for the controlled delivery of β-galactosidase into intestines. Issue 35 (23rd August 2018) - Pavel, Ileana-Alexandra; Girardon, Maxime; El Hajj, Sarah; Parant, Stéphane; Amadei, Federico; Kaufmann, Stefan; Tanaka, Motomu; Fierro, Vanessa; Celzard, Alain; Canilho, Nadia; Pasc, Andreea
Abstract : Coating of mesoporous silica carriers with dioleoylphosphatidylcholine allowed triggering of the selective delivery of functional enzymes by lipolysis under simulated intestinal conditions. Abstract : β-Galactosidase has been drawing increasing attention for the treatment of lactose intolerance, but its delivery has been impeded by degradation under gastric conditions. We have demonstrated that the coating of mesoporous silica microparticles (diameter ≈ 9 µm, pore size ≈ 25 nm) with dioleoylphosphatidylcholine membranes significantly improved the loading capability and protected the enzymes from the loss of function under simulated gastric conditions. Once the particles are transferred to simulated intestinal conditions, the digestion of phosphatidylcholine with pancreatin led to the release of functional β-galactosidase. The coating of mesoporous silica nanoparticles with a single phospholipid bilayer opens up a large potential towards the controlled release of orally administrated drugs or enzymes to the intestines.